Morphology Transformation of Foldamer Assemblies Triggered by Single Oxygen Atom on Critical Residue Switch (Small 36/2021). Issue 36 (9th September 2021) - Oh, Byung‐Chang; Yoon, Eunyoung; Gong, Jintaek; Kim, Jaewook; Driver, Russell W.; Kim, Yongjun; Kim, Woo Youn; Lee, Hee‐Seung
Abstract : Morphology Transformation The molecular‐level information installed in a given foldamer is coherently transmitted to the morphologies of the foldamer morphology transformation assemblies at the micrometer scale. In article number 2102525, Hee‐Seung Lee and co‐workers demonstrate a stepwise morphology transformation, from the molar‐tooth shape to gels via rectangular and truncated tilted prism shapes, to create biofunctional assemblies with nonspherical shapes.